Double Threat of Indonesian Maternal Health During The Pandemic of Covid-19 - Astri Nurdiana; Uway Wariah; Irma Yanti (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
The high maternal mortality rate is a complex health challenge reported in Indonesia long before the Covid-19 pandemic. However, the challenge of reducing the number of deaths has increased with the pandemic. This research was a descriptive-analytic study using a retrospective cohort design. The population in this survey was 96 mothers from 30 districts in Karawang who went through pregnancy, postpartum, newborn, and family planning experiences between February-May 2020. Therefore, data were collected through virtual interviews with the use of a questionnaire as the research instrument. The highest score was far below 77, with a value 66 and 45.99 average, as shown in the result. The bivariate analysis also showed the influence of participants' last education on the new normal adaptation score with a P-value of 0.006. However, terminating the transmission of the Covid-19 virus in Karawang regency is focused not only on the educational efforts of the health workers but also on enhancing people's self-awareness about the necessity of personal hygiene and hand hygiene, and prenatal consultation.